PENGARUH JENIS KEDELAI, WAKTU DAN SUHU PEMERAMAN TERHADAP KANDUNGAN PROTEIN TEMPE KEDELAI - Mukhoyaroh, Hanifah (Jurnal Florea, 2015)
Tempe is a traditional Indonesian food made by fermentation or fermentation using Rhizopus sp. Tempe is made from soybeans with high protein content. Tempeh-making process is influenced by severalfactors: temperature, humidity and curing time study aims to analyze the influence of soybeans, time,and temperature curing of the protein content of soybean tempe, as a biochemistry lab manual. Theresearch method uses an experimental approach with three replications. Test material using a blackand yellow soybeans type of treatment in this study is a type of soybean yellow and black, with a curingtime of 18 hours and 36 hours, at a temperature of 100o C and 310o C. The protein content was testedusing formol. The results showed black soybean with a temperature of 100o C within 36 hours the highestprotein content of 0.72%. Low protein content of the black soybean with a curing temperature of 310oC curing time of 36 hours.Keywords: soybean, temperature, protein